THE HISTORY OF ISLAMIC RELIGIOUS EDUCATION AND ITS APPLICATION IN THE DYNAMICS OF ISLAMIC EDUCATION IN THE MODERN ERA - Fakhirah Fakhirah; Fatimah Saguni; Adawiyah Pettalongi; Gusnarib Gusnarib (Jurnal Konseling Pendidikan Islam, 2026)
Global social transformation and the development of science in the modern era require the Islamic education system to continuously undergo conceptual reconstruction to remain relevant to the needs of the times. In the Indonesian national context, Islamic Religious Education faces challenges in the form of social change, pluralism, and demands to strengthen moderate, rational, and contextual Islamic values ​​in the world of education. These conditions demonstrate the urgency of genealogical studies to trace the historical roots, development of thought, and conceptual transformation of Islamic Religious Education so that it can be understood comprehensively within the dynamics of contemporary Islamic education. This study aims to analyze the genealogy of Islamic Religious Education and examine its actualization in the dynamics of Islamic education in the modern era. This study uses a qualitative approach with a literature study type. Data sources were obtained from books, scientific journal articles, and relevant academic documents. The data collection technique was carried out through documentation studies, while data analysis used descriptive analytical content analysis techniques. Data validity was carried out through source triangulation and strengthening reference studies. The results of the study indicate that the genealogy of Islamic Religious Education was formed through a long historical process from the classical Islamic scientific tradition to its integration into the modern education system, which was then actualized through strengthening the values ​​of moderation, integration of knowledge, and a contextual pedagogical approach. These findings provide theoretical implications for the development of Islamic Religious Education studies and practical implications for strengthening the adaptive orientation of Islamic education to changing times.